Waste simplification for warehouse using Boolean logic - Sarifudin, M. S.; Mansor, M. A.; Safiei, W. (Penerbit Universiti Malaysia Pahang, 2019)
Warehouse accumulates non-value added or wastes activities consist of inventory, waiting and transportation. The warehouse is a must to prevent any unforeseen events causing failures to implement the Just-In-Time concept. However, the existence of the warehouse will increase the operation expenditure and can lead to the profit losses. Therefore, the manufacturer needs to identify and eliminate the wastes to reduce the consumption of the resources and keep minimum requirement of the activities such as inventory, waiting and transportation in the warehouse. Value Stream Mapping is one of the Lean tools as an approach to eliminate the non-value added or wastes. This tool visualizes the information and material flow of the manufacturing activities. The development of a model based from Value Stream Mapping determined the current state of the wastes existed in the warehouse activities. The model is used to identify and eliminate the waste in the warehouse. From the information flow, the optimum combination of the wastes was determined through Boolean concept. The wastes are simplified and combined by passing through the Boolean operators consist of AND Gate and OR Gate. The expected outcome of this paper is to propose a conceptual model of new value stream mapping to identify and eliminate the waste in the warehouse. From the removal of wastes, the profit can be increased by reduction of the operation expenditure of the manufacturer.